Developing small web based systems - Costa, C. J. (2018)
In this paper it is proposed a website engineering process. The proposed process is largely supported in the concept of usability. But it incorporates concepts of software engineering, specifically simplified. This simplification results from the need of applying to small site development. The approach was applied to a site used by an accounting team.